Dynamic simulation of a load system driven by two identical PMDC motors - Atalay, Ahmet Kubilay; Kocabas, Derya Ahmet; Basdogan, Seda (Видавництво Львівської політехніки, 2013)
In this study, dynamic simulation of a load system driven by two identical permanent magnet direct current (PMDC) motor is performed by MATLAB / SIMULINK. In the dynamic simulation, two equivalent motors are tandem operated both at same voltage and different voltages in order to drive a mechanical load. The current of each motor, total induced torque and steady state speed of the entire drive system are obtained. It is seen that, when the motors are supplied by the same voltage they share the load equally. On the other hand, if they are operated with different voltages, the motor which is supplied with lower voltage always operates as a generator and the motor which is supplied with higher voltage is overloaded in order to supply the other one and drive the mechanical load.
Keywords: pmdc motor; mathematical model; dynamic simulation; tandem operation